Inclusive Lucky Labeling of Graphs (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
we define a new notion called inclusive lucky labeling (ILL) and study proper inclusive lucky labeling (PILL) for simple undirected graphs. We also define inclusive lucky number and proper inclusive lucky number for some simple graphs.